Metagenomics of Coral Reefs Under Phase Shift and High Hydrodynamics - Meirelles, Pedro Milet; Soares, Ana Carolina; Oliveira, Louisi; Leomil, Luciana; Appolinario, Luciana Reis; Francini-Filho, Ronaldo Bastos; de Moura, Rodrigo Leão; de Barros Almeida, Renato Tenan; Salomon, Paulo S.; Amado-Filho, Gilberto Menezes; Kruger, Ricardo; Siegle, Eduardo; et al. (Frontiers in Microbiology, 2018)
Local and global stressors have affected coral reef ecosystems worldwide. Switches from coral to algal dominance states and microbialization are the major processes underlying the global decline of coral reefs. However, most of the knowledge concerning microbialization has not considered physical disturbances (e.g., typhoons, waves and currents). Southern Japan reef systems have developed under extreme physical disturbances. Here, we present analyses of a three-year investigation on the coral reefs of Ishigaki Island that comprised benthic and fish surveys, water quality analyses, metagenomics and microbial abundance data. At the four studied sites, inorganic nutrient concentrations were high and exceeded eutrophication thresholds. The dissolved organic carbon (DOC) concentration (up to 233.3 μM) and microbial abundance (up to 2.5x1055 cell/mL) values were relatively high. The highest vibrio counts coincided with the highest turf cover (~55-85%) and the lowest coral cover (~4.4-10.2%) and fish biomass (0.06 individuals/m2). Microbiome compositions were similar among all sites and were dominated by heterotrophs. The algal/turf dominance found across the region hints that possible synergistic effects of high hydrodynamics, crown-of-thorns starfish (COTS) outbreaks, eutrophication and overfishing are driving coral decline.